Application of the Brainstorming Discussion Method as a Support for Public Speaking Learning for Santri API ASRI Tegalrejo Magelang - Rika Mulia Ningsih; Siswanto (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Learning public speaking is an important aspect of developing public speaking skills for students in Islamic boarding schools. In this context, the brainstorming discussion method emerged as an innovative approach to improve speaking ability and creativity. This research aims to explore the effectiveness of applying the brainstorming discussion method in teaching public speaking at the API ASRI Islamic Boarding School Tegalrejo Magelang. The research method used is qualitative analysis based on observation and interviews. The research results show that the brainstorming discussion method is effective in stimulating the active participation of students, broadening their horizons, and increasing their confidence in public speaking. Students show better abilities in generating creative ideas and conveying messages clearly after participating in this program. However, the challenges of program implementation and sustainability need further attention. The implications of this research provide a basis for further development in the context of Islamic boarding school education and emphasize the importance of using the brainstorming discussion method in learning public speaking for Islamic boarding school students.